The species diversity and composition of seedlings for degraded land rehabilitation in different phytogeographical regions in Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wirnoyo, Lukman AH, Nurliana S. 2022. The species diversity and composition of seedlings for degraded land rehabilitation in different phytogeographical regions in Indonesia. Biodiversitas 23: 5771-5781. Forest clearing and conversion into cropland without implementing conservation measures have caused land degradation. The total area of degraded land in Indonesia is 14 million hectares. The responsible institution for land rehabilitation in Indonesia is Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung (Agency for Watershed and Protection Forest Management), abbreviated as BPDASHL. This study aimed to analyze seedlings' species diversity and composition for degraded land rehabilitation provided by six BPDASHLs located in different phytogeographic regions, i.e., Sunda Shelf, Wallacea, and Sahul Shelf. Data were collected through questionnaires distributed to BPDASHL offices in Papua, West Papua, Gorontalo, Bangka Belitung Islands, Riau, and Aceh. They were analyzed to determine the species richness, indexes of species diversity, equity, and similarity. The clustering of sites based on species composition was done using a dendrogram. This study found that the species richness of seedlings in each site ranged from 25 to 47, the diversity index of Shannon from 2.39 to 2.96, and a Simpson diversity index from 0.80 to 0.94. The species composition differed from one site to another, with similarity indexes of Bray-Curtis and Jaccard of < 0.35. The dendrogram separated western Indonesia (Sunda Shelf) from eastern Indonesia (Sahul Shelf and Wallacea), except for Bangka Belitung Islands, which was clustered in eastern Indonesia despite its location in western Indonesia. Three study sites had more native dominant species, while the other three had more introduced dominant species. We recommend that more native species of seedlings should be provided.